Early results of liver resection due to metastases of colorectal carcinoma - Koprivica Radenko; Radević Božina; Tošović Goran; Koprivica Ranka; Smiljanić Radmila (Vojnosanitetski Pregled)
Background/Aim. Liver metastases are most frequently the result of colorectal carcinoma. The aim of this study was to analyse early results of operative treatment of the patients with the liver metastases of colorectal carcinoma. Methods. This retrospective, prospective study included 387 patients with colorectal carcinoma operated during the period from 2005-2007. All the patients were submitted to oncologic surgery protocol. The functional state of the liver was assessed, especially in the patients with hemotherapy. Diagnostic protocol further included color Doppler ultrasonography of the liver and port system, as well as spiral computed tomography includy angiography. Nine (5.7%) of the patients were submitted to explorative laparotomy. Results. Of all the patients 157 (40.6%) had metastases in the liver, synhronous 78 (20.15%) and metachronous 79 (20.45%), Forty two (26.7%) patients were indicated for the liver resection. In 33 (21%) of them it was performed successfully. There were 18 females and 15 males of the average age 60.09 (42-81) years. Up to 4 metastases had 90.9% of the patients and in 9.09% had up to 5 and more metastases. On average, metastases occupied 2.6 of the liver segments. There were 21.2% of solitary lesions (7 patients), 63.6% of multilple unilobular (21 patients) and 15.15% of multiple bilobular metastases (5 patients). Liver resection was done using ultraharmonic scalpel. At spacious liver resections we used a device for intraoperative saving of blood (cell saver) and applied a technique of selective hepatic vascular exclusion. An average disease-free interval was 16.7 months. There were 60.6% of anatomical liver resections and 39.4% of atypical resections. In 31.1% of the operated patients we made resection on up to two segments of the liver and in 30.3% we made resection of four segments. An average number of segments where resection had been performed was 2.65 and the duration of operation was 143 minutes. In 39.4% of the cases we used a technique of liver vascular isolation, an average duration was 38 minutes. In 30.3% of resections we used cell saver and 70% of operated patients were transfused. On average, 493 ml of blood was transfused. Of the total number of resections, 90.9% was of the type R0, 9.09% of the type R1. An average duration of postoperative hospitalization was 10.6 days. Operative morbidity rate was 15.15% and operative mortality 3.03%. During a six-month observing there were not any mortality or repeated metastases in liver. Conclusion. Anatomic liver resection including selective vascular hepatic excision by the use of an ultraharmonic scalpel and cell saver is considered to be efficient and secure method for the reduction of intraoperative and postoperative complications rendering good surgical results.